Students’ Training Program : Dealing With Scientific Paper (Thesis) - Uyun Nafiah; Suraida; Husarida; Ahmad Ansori; Susi Pransiska; Yahuda (Cv. Utility Project Solution, 2022)
Scientific paper writing training program through Community Service (PKM) activities aim to train students of the Islamic Banking study program, Islamic Economics Law study program, and Islamic Economics study program STIE Syari'ah Al-Mujaddid Tanjung Jabung Timur to write their scientific papers in accordance with the ethics of writing scientific papers. Before executing the PKM, the PKM team announced the planned activities via social media and contacted STIE Syari'ah Al-Mujaddid directly. From the results of the community service implementation team's discussions with STIE Syari'ah Al-Mujaddid, it was determined that the fundamental problems faced by STIE Syari'ah Al-Mujaddid students were as follows: Students' inability to complete the Final Project on time resulted from a variety of deficiencies and motivations in their thesis writing methods, as well as a lack of motivation to write and knowledge of the technical aspects of writing correctly (Thesis). Students do not understand the Technique and Preparation of Thesis Proposals, the distinction between a thesis and an article, nor how to locate reference sources.This service involves all students of semester VII (Seven) who are required to make scientific work as a final project to hold a bachelor's degree. This activity is carried out using the method of observation, lectures, and practice, as well as evaluation. The results of this activity are that participants gain knowledge about how to write their scientific paper in accordance with the ethics of writing scientific papers and avoid plagiarism.